Efektivitas Pendidikan Kesehatan Melalui Media TikTok terhadap Tingkat Pengetahuan dan Sikap Ibu Hamil tentang Antanatal Care di Puskesmas Mrican Kota Kediri - Chintia Dewi Permatasari; Rahajeng Siti Nur R; L. A Wijayanti; Ira Titisari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2026)
Antenatal care (ANC) plays an essential role in reducing maternal and infant mortality. However, there is still a gap in ANC visits between K1 and K4, which may be influenced by the knowledge and attitudes of pregnant women. TikTok, as a widely used social media platform, has the potential to become an innovative educational tool. This study aimed to determine the effectiveness of health education through TikTok in improving pregnant women's knowledge and attitudes regarding ANC. The research design used was pre-experimental with a one-group pretest-posttest design. A total of 51 pregnant women were selected using simple random sampling. The instruments included educational TikTok videos and structured questionnaires on knowledge and attitudes. Data analysis was conducted using the Wilcoxon Signed Rank Test. Results showed a significant increase in both knowledge and attitudes after the TikTok-based health education intervention, with p-values < 0.05. In conclusion, TikTok is effective as a media for health education to enhance pregnant women’s understanding and attitudes toward antenatal care.